Machines désirantes : des sexbots aux OS amoureux - Anthony Masure; Pia Pandelakis (ReS Futurae)
Our goal is to take an in-depth look at the representation of sexual desire and sexual practices as they exist or may exist between machines and human beings. In our daily experiences, the desire to interact sexually with a machine can be met with deception or frustration whereas sex and technology creativally overlap in sci-fi films. This opens interesting and challenging vistas, such as the emblematic figure of the sexbot. In the context of product design, the sexbot remains close to the passive sextoy. However, film and TV productions offer the possibility, for the machine (be it a robot, a computer or an artifical intelligence) to not solely be desired and to become an active desiring subject (a “desiring-machine“, according to Deleuze and Guattari). From the remote controlled women of Stepford Wives to the bodiless intelligence of Her, we will try to account for the broadth of the imaginaries involving computer and sex practices, as well as the possibilities for their recreation in the context of design projects.